National Treatment in the GATT - Horn, Henrik (American Economic Review, 2006)
The National Treatment (NT) clause is the first-line defense in the GATT (and in most other trade agreements) against opportunistic exploitation of the inevitable incompleteness of the agreement. This paper examines the role of NT as it applies to internal taxation under the GATT. It is shown that despite severely restricting the freedom to set internal taxes, NT may improve government welfare, but it will not completely solve the incomplete contract problem it is meant to remedy. Furthermore, it requires a high degree of economic sophistication on behalf of trade negotiators in order for this beneficial effect to materialize.